Pre-Service Physics Teachers' Physics Understanding and Upper Primary Teacher Education in Ethiopia - M. Alemu; M. Tadesse; K. Michael; M. Atnafu (University of Sofia, 2019)
In this study attempt was made to explore the challenges of physics teacher education in Ethiopia based on data collected from 16 Teacher Education Colleges, 432 pre-service physics teachers in their final year of study, and 31 college lecturers. From the qualitative and quantitative analysis of conceptual test results, attitude questionnaire, interviews, and classroom videos the following major results were found. At the end of one-year intervention with dialogic teaching, both the comparison and treatment pre-service teachers were found to score very low in selected TIMSS items from population 2 tests. Pre-service teachers slightly but significantly favored dialogic over didactic and naïve in-quiry teaching but showed significant shift from dialogic to the other two after the intervention. Physics teacher education lecturers predominantly used the lecture method in their classrooms but intervention found to shift their style significantly to dialogical teaching. Finally, it was found that pre-service teachers learning is highly influenced by weak English language proficiency, low motivation, and expectation of low social status for the teaching profession